Mobile Banking and Technical Efficiency of Commercial Banks in Kenya - Getugi, Joyce Chepkoech; Osoro, Cliff; Kihara, Allan (Journal of Accounting, 2023)
Purpose: The financial sector is being revolutionized as a direct result of technological progress, with banks and other financial institutions embracing new technologies to better serve their customers online. Technological developments in the financial sector are simplifying access to financial services. The study set out to dissect the effects of Fintech on Kenya's commercial banking sector. The general objective was to establish the effect of mobile banking on technical efficiency of commercial banks in Kenya. The study was anchored on Theory of Constraint-Induced Innovation. Methodology: The entire study relied on collecting empirical data and evaluating hypothesis in a positivist way. A causal-comparative research design was used in this research. The study targeted population of Seventeen Kenyan commercial banks from the first and second tiers. The analysis relied on secondary sources of information. The gathered quantitative data was analyzed using both descriptive and inferential statistics. Numbers, medians, and standard deviations were used to characterize the data, and frequency distributions were used to determine the sample size. Models for analyzing correlations and regressions are inferential statistics. STATA was used for the data analysis. Findings: The study established that mobile banking has a positive and significant effect on technical efficiency of commercial banks in Kenya. Unique contribution to theory, practice and policy: Commercial banks in Kenya are recommended to improve their mobile banking services in light of the study's findings.